Komparasi COBIT 2019 dan ISO 27001 Terhadap Audit ISO 21001 untuk Akurasi Rekomendasi Audit SI/TI Pendidikan - Anggraeni, Retno Setya; Rochim, Adian Fatchur; Widodo, Aris Puji (Diponegoro University, 2025)
ISO 21001 refers to the standardization of educational organization management and is an international standard, making it mandatory to be implemented in higher education institutions. Along with this, the rapid development of Information Systems and Information Technology (IS/IT) today has changed the paradigm of education and provided a new perspective that IS/IT support not only aids the learning process but also various other areas in higher education. Standardization focusing on this field includes IT Governance (ITG) COBIT 2019 and ISO 27001. Therefore, the researcher conducted a study to analyze which tools are most correlated with the implementation of ISO 21001, so that the findings of this research can provide recommendations that can serve as a basis for policy in selecting the appropriate standardization tools. The research method used is ex post facto. The analysis was conducted using SmartPLS. The researcher designed a questionnaire instrument to be distributed to the population of the Department of Computer Engineering and Informatics Engineering, UNDIP Semarang. The results of the questionnaire will then be tested for validity and reliability, followed by a correlation test while considering the T-Value. Based on the analysis results, it was concluded that both COBIT 2019 and ISO 27001 have an influence on ISO 21001. The influence of COBIT 2019 on ISO 21001 is significant, with a path coefficient and p-value of 0.000, while the influence of ISO 27001 shows a p-value of only 0.091.